2010
DOI: 10.1007/s10566-010-9094-6
|View full text |Cite
|
Sign up to set email alerts
|

D-Cycloserine Augmentation of Cognitive-Behavioral Therapy: Directions for Pilot Research in Pediatric Obsessive-Compulsive Disorder

Abstract: This paper discusses a recent translational success in combining behavioral psychotherapy with a novel medication, d-cycloserine (DCS), to augment cognitivebehavioral therapy (CBT) for anxiety disorders. The literature on behavioral theory of exposure-based therapies is provided, followed by a discussion of the role of DCS in enhancing extinction learning that is core to such therapies. As well, pragmatic issues such as dosing and timing are discussed. The manuscript is concluded with consideration of future d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 79 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…In fact, research suggests that it may lose its cognitive‐enhancing properties if prescribed over prolonged periods (e.g., Norberg, Krystal, & Tolin, 2008). Finally, unlike many psychotropic medications, the side‐effect profile of DCS is minimal (e.g., Storch et al., 2010a). The side‐effect profile of DCS is equivalent to taking a dose of antibiotic.…”
Section: D‐cycloserine As a Cognitive Enhancer For Augmenting Exposurmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, research suggests that it may lose its cognitive‐enhancing properties if prescribed over prolonged periods (e.g., Norberg, Krystal, & Tolin, 2008). Finally, unlike many psychotropic medications, the side‐effect profile of DCS is minimal (e.g., Storch et al., 2010a). The side‐effect profile of DCS is equivalent to taking a dose of antibiotic.…”
Section: D‐cycloserine As a Cognitive Enhancer For Augmenting Exposurmentioning
confidence: 99%
“…These participants were defined as “treatment refractory.” Participants are randomised to nine sessions of CBT, including five sessions of ERP (sessions 5–9) with DCS ( n = 9) or with a placebo ( n = 9). As in the Storch et al. (2010a) paediatric study, this study uses two doses dependent on child weight, such that children weighing between 25 and 45 kg take 25 mg of DCS (0.56–1.0 mg/kg/day) and children weighing 46 kg and above receive 50 mg of DCS (0.56–1.08 mg/kg/day).…”
Section: Childhood Ocd and D‐cycloserine‐augmented Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a large-scale study of paediatric psychotropic prescribing practices, researchers found that at younger ages, boys were more likely than girls to receive psychotropic medications; however, at older ages this relationship was reversed (Hong & Shepherd, 1996). Unlike many psychotropic medications used to treat children, DCS is considered to be a very low-risk intervention, with the potential for adverse effects being described by Storch et al (2010) as 'almost negligible'. A possible risk raised by some researchers is that DCS could inadvertently strengthen the fear memory, should fear extinction fail to occur during exposure therapy (e.g., Hofmann, 2014).…”
mentioning
confidence: 99%
“…Considering that some children experience significant residual OCD symptoms following an adequate trial of CBT and SSRI (POTS 2004;Freeman et al 2008), the importance of an empirically based second-and third-line treatment algorithm cannot be overstated. Storch et al (2010) highlight a particular augmentation strategy, discussing how D-cycloserine (DCS) might increase the efficacy of exposure-based therapy by enhancing extinction learning. Several DCS studies have been conducted in adults with OCD, suggesting that this agent can enhance the efficiency of exposure therapy (Abramowitz et al 2009;Norberg et al 2008).…”
mentioning
confidence: 99%